Legalitas Transaksi Bagi Orang Yang Mengalami Retardasi Mental Menurut Mazhab Syafi’i dan Hanafi (Studi Putusan No : 32/Pdt.g/2011/PN.BNA) - Sri Ayu Agustina; Ema Fathimah; Bitoh Purnomo (Muqaranah, 2022)
People who have limitations such as weakness of mind must be under guardianship in doing everything, including carrying out transactional activities. Because, without guardianship it is feared that it will have a bad impact on both himself and others. Therefore, researchers conducted research with the aim of examining the legality of buying and selling transactions carried out by people who have mental limitations. This research specifically examines the judge's decision on related cases. The study will focus on the views of scholars. This study uses a normative and comparative juridical approach with library research methods. The results of the study show that there are differences of opinion regarding the legality of transactions carried out by people with mental disabilities. There are those who think it is legal and there are also those who think it is illegal. People who have mental limitations must involve their guardians if they want to make buying and selling transactions, this is based on the concept of al-hajr. This is intended so that the transaction does not cause harm to both himself and others.